Single versus tandem high‐dose melphalan followed by autologous blood stem cell transplantation in multiple myeloma: long‐term results from the phase III GMMG‐HD2 trial. (17th March 2016) - Mai, Elias K.; Benner, Axel; Bertsch, Uta; Brossart, Peter; Hänel, Annette; Kunzmann, Volker; Naumann, Ralph; Neben, Kai; Egerer, Gerlinde; Ho, Anthony D.; Hillengass, Jens; Raab, Marc S.; et al.
Summary: The prospective, randomized phase III trial GMMG‐HD2 aimed at demonstrating non‐inferiority of single (Arm A) versus tandem (Arm B) high‐dose melphalan followed by autologous transplantation (HDM/ASCT) with regard to 2‐year event‐free survival (EFS) in newly‐diagnosed multiple myeloma (MM) and included 358 evaluable patients [Intention‐to‐treat population, (ITT), single/tandem HDM/ASCT: n = 177/181]. After a median follow‐up of more than 11 years, non‐inferiority of single versus tandem HDM/ASCT was demonstrated using the planned non‐inferiority threshold of 15% of the 2‐year EFS rate. Neither EFS ( P = 0·53) nor overall survival (OS) ( P = 0·33) differences were observed in the ITT population. In the tandem arm, 26% ( n = 47/181) of patients refused a second HDM/ASCT due to non‐medical reasons. A per‐protocol (PP) analysis, including patients who received the intervention (single/tandem HDM/ASCT: n = 156/93) and patients who did not receive a second HDM/ASCT due to medical reasons (12%, n = 22/181), did not yield differences in EFS ( P = 0·61) or OS ( P = 0·16). In the ITT and PP set of the tandem arm, the rates of complete responses increased from first to second HDM/ASCT (both P = 0·04). Ten‐year OS for the entire ITT was 34% (95% confidence interval: 29–40%). OS after first relapse was significantly shortened in the tandem arm ( P = 0·04). In this study single HDM/ASCT was non‐inferior to tandem HDM/ASCT in MM.